Analisis Tingkat Kebisingan Aktivitas Jalan Trans Kalimantan Terhadap Rumah Sakit Umum Kota Palangka Raya: Analysis Of Noise Levels Of Trans Kalimantan Road Activities On The General Hospital Of Palangka Raya City - Yosevina, Yosevina; Baktiani, Linda (Media Ilmiah Teknik Sipil, 2024)
High economic growth also indirectly has an impact on increasing vehicle traffic activity on the highway. Noise due to traffic will continue to increase along with the increase in human activity using vehicles.Sound Level Meter (LSM) is a tool used to measure noise at a point. Specifically in this research, namely the noise level of the Trans Kalimantan Road towards the General Hospital of Palangka Raya City. From the data obtained in the research results, it shows that the noise level at the General Hospital of Palangka Raya City due to transportation activities has exceeded the quality standard limits that have been set. From the results of research and data analysis, it was found that the traffic noise level that occurred at the General Hospital of Palangka Raya City at point 1 next to the entrance to the General Hospital of Palangka Raya City was 73.70 dBA and at point 2 in front of the Emergency Room General Hospital of Palangka Raya City was 77. 29 dBA which exceeds the quality standard noise level set for hospital areas, namely 55 dBA. Based on the results of these calculations, it is recommended that the General Hospital of Palangka Raya City make a natural noise barrier, namely in the form of a fence or a thicket of plants with fairly even leaf density or an artificial noise barrier in the form of a soundproof wall, etc. so that the comfort of the hospital can be maintained.